Diuretic effects of aqueous extract of Olive Leaves (Olea europea) in adult male rats. - Abdullah, B. N.; Khudiar, K. K.; Toma, B. S. (The Iraqi Journal of Veterinary Medicine, 2003)
This study was carried out to investigate the effects of aqueous extract of olive leaves (Olea europea) on kidney functions. Eighteen adult male rats three equal groups placed individually in were randomly divided in to metabolic cages and were handled as follows: group (C) served as control group; rats in group (T1) were intubated (90 mg/kg B.W.) of aqueous extract of group T2 were intubated (0.8 mg/kg B.W.) of olive leaves and rats in ammuretic. Blood and urine samples were collected after 24 hours of significant increase in urinary output intubation. The results showed a ions and potassium urinary sodium increase in an by accompanied concentration in the olive leaves treated group only. Creatinine clearance (as an for glomerular filtration rate) increased significantly in both treated index groups, it is concluded that olive leaves extract may cause its diuretic effect by. increasing the glomerulor filtration rate.